The scheduler's balancing act of sensing and reacting: a behavioural perspective on scheduling. Issue 13 (2nd July 2020) - Larco Martinelli, José Antonio; Fransoo, Jan; Gharehgozli, Amir; Wiers, Vincent
Abstract : The scheduler has been extensively studied from the point of view of their schedules, using operations research. However, the scheduler not only fulfils a decision-maker role but also an informational role, responding to requests and disruptions, both from the supply and the demand side. Responding in a timely manner to such requests and disruptions is paramount for the scheduling job. Using a field study with job shadowing of schedulers in a Fortune 500 chemical company, we characterise the scheduler's workflow in a simulation model; this allows us to discriminate between contextual factors of the scheduler's job and behavioural factors inherent to them. Furthermore, it explicitly assesses the effect of increasing the frequency sensing of the outer world on responsiveness. Our findings show that the studied schedulers prioritise sensing activities related to checking emails rather than monitoring for disruptions in a decision support system. Thus, we find a higher potential for relative improvement in terms of responding to possible disruptions shown in decision support systems rather than responding to email requests. Moreover, we show that by adjusting email frequency checking and preemption behaviours, it is possible to revert an out of control situation to finite response times.